Muslim tourist perceived value on satisfaction in Muslim-friendly tourism in Kuala Lumpur and Melaka / Aimi Hajar Abdul Aziz - Abdul Aziz, Aimi Hajar (Faculty of Business and Management, 2020)
Muslim consumerism is rapidly growing and expanding annually in which there is a surge demand on services that caters to Muslim needs especially in the tourism industry. Thus, this research focuses on Muslim Tourist perceived value on satisfaction in Muslim-Friendly Tourism that is, a study on foreign tourist as well as local tourist in Kuala Lumpur and Melaka. Due to a large population, a sample size decision model from Krejcie and Morgan (1970) is used with a target sample size as suggested is 384. However, in this research a total of 400 questionnaires were distributed in targeted states as well as through online platforms. The objectives of this study are to identify the correlation between Muslim Tourist Perceived Value (MTPV) and tourist satisfaction as well as to identify which dimensional factors in MTPV is the most influential factor on tourist satisfaction. The questionnaires were distributed offline to local Muslim tourist and foreign Muslim tourist in areas in Kuala Lumpur such as Kuala Lumpur Conventional Centre (KLCC), Pavillion, and KL Sentral. In Melaka, questionnaires were distributed in Mahkota Parade, Dataran Pahlawan and Klebang. The questionnaires were also distributed online as well in order to find out if MTPV influence Muslim tourist satisfaction in MFT. The result obtained from this study indicate that the most influential factor of this study is cognitive value of emotion, whereby hypotheses H1b, H2a, H3a, H4a are accepted, and hypotheses H1a, H2b, H3b, H4b are rejected. Therefore, this research has been carried out to identify the perceived value that influences satisfaction.